Understanding Generational Differences in Knowledge Sharing - Gunilla Widen; Farhan Ahmad; Tom Siven; Evgenia Ivantsova (United Kingdom, 2025)
Generational traits generally have mixed impact on work activities. From previous research we have a very scattered picture of the impact of generational differences in the workplace context. This paper investigates how generational differences influence the knowledge-sharing behaviour in organizations. Interviews were conducted in two Finnish organisations. Our analysis shows that when it comes to values and priorities in relation to knowledge sharing, there are no differences between younger and older employees. However, the interviews revealed nuances between generations, which explain why generational differences are not so decisive. It was found that professional age is a more important factor when describing differences between employees’ attitudes to knowledge sharing. Furthermore, the organizations’ socialization process plays an important role in overriding generation differences in knowledge sharing. Finally, the interviews underlined that a flexible approach to IT is increasingly important for work tasks in all age groups and generational differences do not matter to a large extent.
ECKM 2020 - Proceedings of the 21st European Conference on Knowledge Management